Macmillan to sell its Indian expertise. (Bookseller, 2004)
Macmillan Group has formed a new division offering e-publishing support services to third party clients, drawing on the resources and expertise of Macmillan India. Macmillan Publisher Services, the new division based in London, England will work with client publishers to account-manage and project-manage a range of services. Jayne Marks has been appointed managing director. She has worked for Macmillan's Nature Publishing Group and Stockton Press. Talks have begun with some potential clients, primarily STM, humanities and social science journal publishers about possible service requirements.